Blood meal as protein ingredient from animal waste product in the diet of (Oreochromis niloticus) - Edeh, Bello; Gbagi, Adeyeye (Advances in Aquaculture and Fisheries Management, 2014)
Three iso-nitrogenous diet of 35% crude protein were prepared with blood meal at various inclusion level of 0, 50 and 100%. These were coded Treatment 1 (T1), Treatment 2 (T2), and Treatment 3 (T3) respectively. The diet with 0% blood meal was used as control. Oreochromis niloticus average initial weight of 6.20±0.02 g were randomly allocated to three treatment diets, 20 fingerlings per unit net-hapa, for a period of twelve weeks (84 days). The three treatment diets (T1, T2 and T3) were replicated in three net-hapas each of dimension 1 × 1 × 1 m, stacked in concrete tanks. Each dietary treatment was tested in triplicate group of 20 fingerlings per unit hapa. The experimental fish were fed twice daily at 5% of biomass for a period of twelve weeks. Final average weight gain, specific growth rate, protein efficiency ratio, protein intake, were highest in the fish fed with 100% BM (T3) inclusion. The analysis of variance showed significant difference P<0.05) in the feed treatments on the growth of (O. niloticus). There were no significant difference (p >0.05) in growth performance among fish fed diets. However, fish fed diet 100% BM (T5) had higher (p<0.05) growth than those fed with 0% (T1) and 50% (T3) BM respectively. There was no mortality recorded during the period of the experiment. The results showed that bloodmeal performed very well as a feedstuff and inclusion of rate of 100% could replace fishmeal in Tilapia diet with no adverse effect on growth and survival of O. niloticus fingerlings.